The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/gene.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

High-density genotyping of immune loci in Kawasaki disease and IVIG treatment response in European-American case–parent trio study

Abstract: Kawasaki disease (KD) is a diffuse and acute small-vessel vasculitis observed in children and has genetic and autoimmune components. We genotyped 112 case-parent trios of European decent (confirmed by AIMS) using the ImmunoChip array and performed association analyses with susceptibility to KD and IVIG non-response. KD susceptibility was assessed using the transmission disequilibrium test whereas IVIG non-response was evaluated using multivariable logistic regression analysis. We replicated SNPs in three gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
(65 reference statements)
1
21
0
Order By: Relevance
“…It is likely that host genetic factors, such as polymorphisms in the Fc gamma receptors, play a role in both the response and resistance to IVIG. 61,202,203 Risk Scores for Predicting Nonresponse to IVIG Approximately 10% to 20% of patients with KD have persistent or recurrent fever after primary therapy with IVIG plus ASA. 204,205 Many studies have shown that patients who are resistant to initial IVIG are at increased risk of developing coronary artery abnormalities.…”
Section: Ivig Resistancementioning
confidence: 99%
“…It is likely that host genetic factors, such as polymorphisms in the Fc gamma receptors, play a role in both the response and resistance to IVIG. 61,202,203 Risk Scores for Predicting Nonresponse to IVIG Approximately 10% to 20% of patients with KD have persistent or recurrent fever after primary therapy with IVIG plus ASA. 204,205 Many studies have shown that patients who are resistant to initial IVIG are at increased risk of developing coronary artery abnormalities.…”
Section: Ivig Resistancementioning
confidence: 99%
“…Recently, in a large genome-wide association study, KD susceptibility in Japanese children was associated with a polymorphism near the HLA-DQA2 locus on 6p21.3 [47]. The association of polymorphisms in HLA/DQB2 and HLD/DOB were recently validated in a study of KD trios of European descent, thus broadening the suspected importance of HLA in KD susceptibility [17]. The role of the HLA in the Fc-specific Treg response is currently under study by our laboratory.…”
Section: Minimal Fc Epitopes For Treg Recognitionmentioning
confidence: 99%
“…There were significantly fewer patients with coronary artery abnormalities in the group receiving prednisolone plus IVIG (3% vs. 23%, CI 0.12–0.28, p<0.001). Caveats to the adoption of this protocol for other countries is that the scoring system has been shown to have poor predictive value in mixed ethnic populations and patients with coronary artery abnormalities on their first echocardiogram at diagnosis were excluded[17, 18]. In a U.S. population, of the patients who go on to develop aneurysms, 81% had an abnormal first echocardiogram and would have been excluded from the RAISE study[19].…”
Section: Ivig Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Parents of KD patients in Japan have two-fold higher prevalence than general populations (Uehara et al , 2003). Additionally, multiple genome-wide association (GWA) and candidate gene studies, including our own, have consistently identified the Fc gamma receptors (FcGRs) as major players in the pathogenesis and treatment response for KD (Khor et al , 2011; Makowsky et al , 2013; Onouchi et al , 2012; Shendre et al , 2014; Shrestha et al , 2012; Shrestha et al , 2011). However, there are reports of other genes that have not been adequately studied, including the human leukocyte antigen (HLA) genes in the major histocompatibility complex (MHC) region.…”
Section: Introductionmentioning
confidence: 99%